2003
DOI: 10.1046/j.0283-9318.2003.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

School nurses’ view of schoolchildren's health and their attitudes to document it in the school health record – a pilot study

Abstract: Scand J Caring Sci;2003; 17; 392-398 School nurses' view of schoolchildren's health and their attitudes to document it in the school health record -a pilot study This study highlights school nurses' view of schoolchildren's health and their attitude to document it in the school health records. A strategic sample of 12 school nurses was interviewed. The interviews were semistructured and analysed with qualitative content analysis. The findings showed that the school nurses' viewed schoolchildren as physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 9 publications
4
65
0
9
Order By: Relevance
“…The view of schoolchildren's health by school nurses across countries ranged in a similar manner. In Clausson's et al (10) opinion, schoolchildren's health is good, because the interviewed school nurses viewed schoolchildren as physically healthy. Larson and Zaluha (21) reported that most often schoolchildren sought medical help from school nurses when they had headache.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The view of schoolchildren's health by school nurses across countries ranged in a similar manner. In Clausson's et al (10) opinion, schoolchildren's health is good, because the interviewed school nurses viewed schoolchildren as physically healthy. Larson and Zaluha (21) reported that most often schoolchildren sought medical help from school nurses when they had headache.…”
Section: Discussionmentioning
confidence: 99%
“…School nurses in Sweden are seeking more analyses of their opinions and their experience. They have indicated the importance of ethics, among other factors, in their work improving children's health and avoiding their growth problems (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…For eksempel var deltakerprosen- (20). Studier fra skolehelsetjenesten har vist at helsesøstre finner det uproblematisk å dokumentere fysisk helse i journalen (21), men sykepleiedokumentasjon kan påvirkes av organisatoriske forandringer (22). En ammekyndig helsestasjon skal ifølge retningslinjene kartlegge ammeforekomsten og arbeide for å fremme amming.…”
Section: Styrker Og Begrensningerunclassified
“…Pozneje vprašalnika nismo spreminjali. Strukturna predstavitev vprašalnika: Zdravstvene težave (17)(18)(19)7) Ugotavljali smo pojavnost zdravstvenih težav pri učencih v šoli in pogostost učiteljevih ukrepanj ob posamezni težavi. Praksa ukrepanja (20) Kakšna je praksa ukrepanja na šolah ob akutni bolezni učenca, poslabšanju kronične bolezni oz.…”
Section: Uvodunclassified